Maritime Security in Southeast Asia: How has ASEAN been Talking About It So Far? - Zulhatta, Agung Imam; Marsetio, Marsetio (Andalas Institute of International Studies UNAND, 2022)
The maritime security dynamics in the Southeast Asian region demand focused attention from ASEAN. Southeast Asia holds significant strategic importance, as evidenced by its waters now serving as Sea Lines of Communication (SLOC) for international shipping. However, this strategic value also exposes the region to various escalating security threats, particularly in the maritime domain, including piracy, Illegal, Unreported and Unregulated (IUU) fishing, Trans National Crime (TNC), and maritime border conflicts. This study sheds light on the dynamics of maritime security issues in the region across various ASEAN meetings and assesses the extent to which ASEAN has prioritized maritime security as a focal point. Through data analysis employing query coding based on Buzzerword in Nvivo, examining formal legal documents, statements, discussions, and news in ASEAN meeting forums, it is evident that ASEAN consistently addresses maritime security issues in the region. This underscores that maritime security is not a widely discussed topic within ASEAN, indicating why minimizing maritime threats in this region proves challenging. The semiotic ideas of Cristian Bueger regarding maritime security further provide insight into additional findings in this research, specifically how ASEAN has historically interpreted the definition of maritime security threats.